In-vitro and in-vivo Immunomodulatory Effect of Polyherbal Suspension on Cyclophosphamide Induced Experimental Animal - Majumdar, Ashish; Shukla, Shiv Shankar; Pandey, Ravindra Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The aim of present investigation was to determine the efficacy of a polyherbal formulation. [Composed of Nelumbo nucifera (NN), Euryale ferox (EF) and Trapa natans (TN)]. Materials and Methods: The seeds of NN and EF and fruits of TN were extracted using hydroethanol (1:1) solvent. The dried extract of each plant was used for phytochemical investigation and DPPH radical scavenging activity to determine antioxidant activity. Polyherbal suspension (PHS) was prepared using dried extracts with other excipients. Acute toxicity study was performed for the PHS before in vivo experiment on animals. Albino Wistar rats were selected for the evaluation of immunomodulatory activity of PHS. Immunosuppression was induced by administration of cyclophosphamide subcutaneously on day 0 in all treated groups and treatment with test drug was continued for 14 days. Results: Results exhibited that extracts showed presence of various secondary metabolites including flavonoids, alkaloids, tannins, amino acids, carbohydrates and starch. The prepared PHS was found safe in acute oral toxicity study with no harm to animal’s up to 2000 mg/kg dose. The percentage inhibition of DPPH radial by NN, EF and TN were 86.67%, 85.78% and 89.88%, respectively at the concentration of 200 μg/mL. PHS showed significant immunomodulatory activity by increasing neutrophil adhesion to 47.94% in 400 mg/kg dose with mean neutrophil percentage of 40.05%. Results of hematological parameters revealed that PHS restored all the levels of blood components in 400 mg/kg dose. Conclusion: Thus, PHS may be used as an effective and safe formulation in the treatment of immune deficiency.
Keywords: Neutrophil adhesion; Phytochemistry; Nelumabo nucifera; Euryale ferox; Trapa natans